Calculation Models for Acoustic Analysis of St. Elizabeth of Hungary Church in Jaworzno Szczakowa - KOSAŁA, Krzysztof (Archives of Acoustics, 2016)
In parallel with research conducted using conventional methods, a uniform index method for assessing the acoustic quality of Roman Catholic churches has been developed. The latest version of the index method has been created using the index observation matrix of 12 churches which have been rated by means of the single number global index.Assessments of the acoustic quality of any Roman Catholic church, using two calculation models: the Global Acoustic Properties Index (GAP) and the Global Index (GI), are shown in the article. The verification was performed on the example of one church, showing the way of calculating global indices to assess the acoustic quality of a new facility. The next stages in the development of the index method for assessing the acoustic quality of churches were taking into account the audience, using simulation tests and determining the spatial distribution of the single number GAP index in an examined church. An attempt to use the GAP and GI calculation models to assess the acoustic properties of some churches is also shown in the article.